Economic Feasibility Analysis of Mining Bussiness Plan CV. XYZ, Golopongkor Village, Komodo District, West Manggarai Regency - KADJI , Robertho (PT Keberlanjutan Strategis Indonesia, 2025)
This research aims to evaluate the economic feasibility of the mining business plan proposed by CV. XYZ located in Golopongkor Village, Komodo District, West Manggarai Regency, with an operational production area of 4.27 Ha. The analysis was conducted using three main indicators, namely Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP) to assess the profitability and feasibility of the investment. The research results show that the positive NPV value of Rp1,130,299,085.00 indicates that the project is capable of providing economic benefits that exceed the initial investment value. The IRR value of 39% and the PBP of 0.7 years reflect a relatively quick capital recovery period. These values indicate that the mining project is economically feasible and provides significant financial benefits. The expected future cash flows exceed the initial investment, and the quick payback period reinforces the recommendation that this project is feasible. With high profit potential and controlled financial risks, this project is deemed capable of contributing to business growth and the operational sustainability of the company.